2021
DOI: 10.3389/fpls.2021.628167
|View full text |Cite
|
Sign up to set email alerts
|

The Resistance of Oilseed Rape Microspore-Derived Embryos to Osmotic Stress Is Associated With the Accumulation of Energy Metabolism Proteins, Redox Homeostasis, Higher Abscisic Acid, and Cytokinin Contents

Abstract: The present study aims to investigate the response of rapeseed microspore-derived embryos (MDE) to osmotic stress at the proteome level. The PEG-induced osmotic stress was studied in the cotyledonary stage of MDE of two genotypes: Cadeli (D) and Viking (V), previously reported to exhibit contrasting leaf proteome responses under drought. Two-dimensional difference gel electrophoresis (2D-DIGE) revealed 156 representative protein spots that have been selected for MALDI-TOF/TOF analysis. Sixty-three proteins hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 111 publications
(135 reference statements)
1
1
0
Order By: Relevance
“…Many evidences illustrate that PLD has an important role in plant tolerance under stress ( Ji et al., 2018 ; Alferez et al., 2019 ; Gnanaraj et al., 2021 ; Wei et al., 2022 ) and adjust plant defense response to osmotic stress ( Liu et al., 2021 ; Liu et al., 2022 ; Hong et al, 2008 ). Our findings indicated that abundance of Phospholipase D was increased under osmotic stress, similar to results of ( Urban et al., 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Many evidences illustrate that PLD has an important role in plant tolerance under stress ( Ji et al., 2018 ; Alferez et al., 2019 ; Gnanaraj et al., 2021 ; Wei et al., 2022 ) and adjust plant defense response to osmotic stress ( Liu et al., 2021 ; Liu et al., 2022 ; Hong et al, 2008 ). Our findings indicated that abundance of Phospholipase D was increased under osmotic stress, similar to results of ( Urban et al., 2021 ).…”
Section: Discussionsupporting
confidence: 90%
“…Hence, different systematic approaches, such as breeding disease-resistant staples with improved nutritional quality, have been employed in plant breeding research programs to meet the dietary needs of the rapidly increasing global population. This has become more imperative considering the drastic reduction in the quantity and quality of global food supply occasioned by environmental pollution, global warming, and the development of novel biofuel sources [1]. In sub-Saharan Africa, maize (Zea mays L.) has been shown to contribute to food security and poverty reduction among low-income families [2].…”
Section: Introductionmentioning
confidence: 99%